The Restrictions of Genre The Television Series The Handmaid’s Tale as a ClassicDystopia - Spiegel, Simon (Journal for Religion, Film and Media, 2024)
While there is a long tradition of literary utopias, there are hardly any positive utopias in film. Cinematic dystopias, by contrast, abound. The typical dystopia usually features a protagonist who is in opposition to the ruling regime, a built-in dramatic conflict that makes dystopias particularly well-suited for films. Although the huge success of Hulu’s THE HANDMAID'S TALE seems to confirm the affinity between film and dystopias, the show also highlights that a series spanning multiple seasons has very different dramaturgical demands than a feature film. Those demands are at odds with the narrative structure of a typical dystopia. While the standard rebellion plot provides the needed tension, it cannot be prolonged endlessly. Sooner or later the rebellion either succeeds or fails, at which point literary dystopias normally end. A series like The Handmaid’s Tale needs to be able to continue that plot, which is theprimary reason why the protagonist Offred never leaves Gilead despite having several opportunities to do so.